Oleophylic sepiolite as well as preparation method and application thereof
By combining thermal activation treatment and dry ball mill modification technology, oleophilic sepiolite was prepared, which solved the problems of high energy consumption and poor modification effect of clay mineral modification process in the prior art, and achieved an efficient and simple dry modification process, which improved the performance and production efficiency of the material.
Patent Information
- Application Number
- CN202510243540.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the wet modification process of clay minerals has problems such as high energy consumption, high equipment requirements and poor modification effect, and there is a lack of a simple and efficient preparation method for dry organic modified clay.
By combining traditional thermal activation treatment and dry ball milling modification, sepiolite and stearic acid are premixed and heated in a ball milling tank until the stearic acid melts, and then the modifier γ-aminopropyltriethoxysilane is added for ball milling to obtain lipophilic sepiolite.
This method shortens the process flow and improves production efficiency. The modified clay materials obtained have high practical production guidance significance, can significantly improve the surface area and modification effect of sepiolite, and are suitable for large-scale industrial production.
Smart Images

Figure CN119708637A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-metallic material preparation, and particularly relates to an oleophilic sepiolite and a preparation method and application thereof. Background Art
[0002] Clay minerals are an important class of mineral resources, characterized by unique micro- and nanostructures, large specific surface areas, and excellent thermal and chemical stability. Some clay minerals also exhibit excellent ion exchange properties, making them widely used in environmental remediation, machinery manufacturing, petrochemicals, and other fields. Clay minerals are layered hydrous silicates or aluminosilicates with grains smaller than 2 μm, found in clay or clay rock. Their chemical composition primarily consists of H₂O, SiO₂, and Al₂O₃. Some also contain Fe₂O₃, MgO, and smaller amounts of K₂O and Na₂O. Their crystal structure primarily consists of two basic layers: a silicon-oxygen tetrahedral sheet (T layer) and an aluminum (magnesium)-oxygen octahedral sheet (O layer). These two layers, when combined in appropriate ways, form unit cells of either the 1:1 or 2:1 type. The two unit cells are freely combined, and different superposition methods form different clay minerals. The main clay minerals are kaolinite, montmorillonite, sepiolite, attapulgite, illite and halloysite.
[0003] Organic modification of clay surfaces involves adding organic modifiers to alter the hydrophilic and hydrophobic properties of the clay surface, thereby enabling the clay to bond effectively with hydrophobic substrates. Modifiers primarily include coupling agents, higher fatty acids and their salts, unsaturated organic acids, silicone oils, and polyolefin oligomers. Organically modified clay minerals, due to their unique physical and chemical properties and broad application prospects, play an important role in a variety of fields, including environmental pollution control and remediation, building materials, batteries, medicine and pharmaceuticals, chemicals, and catalysis.
[0004] Regarding modification, Chinese patent publication CN 116253329 A discloses a method for preparing a mixed-dimensional attapulgite clay-based lubricant friction-reducing additive, belonging to the technical field of organically modified clay preparation. This invention involves crushing and desanding the mixed-dimensional attapulgite clay, then dispersing it in a mixed solution of inorganic and organic acids to react and produce activated mixed-dimensional attapulgite clay. This clay is then modified with a lubricant base oil and an ester or ether-based compound as a composite modifier and ball-milled to produce the lubricant friction-reducing additive. This method combines acid activation, wet modification, and ball-milling in separate steps, with the preparation process involving multiple steps of dissolution, solid-liquid separation, washing, and drying. Chinese patent publication CN 114950348 A discloses a process for organically modifying the surface of attapulgite clay. The process involves acid treatment to remove surface impurities and evenly distribute pores. The surface of the attapulgite clay is then organically modified using a surface corrosion method, depositing a layer of carboxymethyl cellulose-modified sulfided nano-zero-valent iron, further enhancing the clay's reduction activity and adsorption capacity. This method also utilizes acid activation and wet modification, and the preparation process involves multiple steps of stirring, mixing, centrifugation, filtration, washing, and vacuum freeze-drying.
[0005] The master's thesis titled "Study on the Modification of Sepiolite and Its Effect on the Performance of Ammonium Nitrate" studied the effects of various modifiers on the organic modification of sepiolite, and applied the organically modified sepiolite as a modifier to ammonium nitrate. The experimental design also adopted a process of reaction, washing, filtration, and drying of sepiolite and modifier solution in the stage of modifying sepiolite, while the process of ball milling sepiolite and ammonium nitrate was adopted in the stage of modifying ammonium nitrate. The moisture absorption rate of the final ammonium nitrate product was greatly reduced.
[0006] The three patents and papers on organic surface modification of clay mentioned above all utilize a wet modification process for clay minerals, which involves multiple steps. This process requires a significant amount of energy for washing and drying, resulting in high energy consumption and high requirements for machinery and equipment. In contrast, the dry modification process is shorter, simpler to operate, requires no additional solvents, and significantly increases the utilization rate of the modifier.
[0007] Chinese patent publication CN 115780801 A discloses a method for preparing a ball-milled carbon nanotube-modified aluminum-based composite material at high temperature. The method involves premixing carbon nanotubes with copper powder, placing the mixture with an aluminum ingot in a ball mill, heating the mill, and then ball milling the mixture. After milling, the mixture is filtered to obtain the ball-milled carbon nanotube-modified aluminum-based composite material. This method combines traditional powder metallurgy and stir casting, leveraging the advantages of both technologies to significantly improve preparation efficiency while maintaining the material's superior performance.
[0008] Chinese patent publication CN 112138705 A discloses a high-temperature and ball-milled modified SBA-15 molecular sieve material and its preparation method, as well as a propane dehydrogenation catalyst and its preparation and application. In the presence of a protective gas, the SBA-15 molecular sieve material undergoes a first-stage heating treatment and a second-stage heating treatment, followed by ball milling of the high-temperature-treated SBA-15 molecular sieve material in a ball mill. The resulting modified SBA-15 molecular sieve material, when used to prepare a propane dehydrogenation catalyst, exhibits high propane conversion and propylene selectivity. Both patents utilize a preheating followed by ball milling process for synthesizing modified aluminum-based composite materials and modified SBA-15 molecular sieve materials, respectively. Currently, there are no known processes for simultaneously applying high temperature and ball milling to modify clay mineral materials.
[0009] Friction materials are complex, multi-component systems. To meet the design requirement of maintaining a stable friction coefficient across various temperature ranges, reinforcing fibers play a crucial role. Current materials used for friction material reinforcing fibers, such as potassium titanate whiskers, glass, Kevlar, carbon, aramid, and basalt, still face challenges such as high cost, weak bonding with resins, low-frequency noise generation, damage to the coupling, and rapid temperature rise. Clay minerals can address some of these issues.
[0010] In terms of application: Chinese patent document CN 117887204 A discloses a friction material, a brake pad prepared therefrom, and its preparation method and application. By modifying polyphenolic resin and carbon fiber separately, a core-shell structure of phenolic resin and modified carbon fiber grafted with sepiolite powder is formed, which synergistically improves the high temperature resistance and wear resistance of the friction material. However, the patent does not effectively and reasonably modify the sepiolite, resulting in a weak bonding performance between the sepiolite and phenolic resin, which in turn affects the performance of the friction material. Chinese patent publication CN 117448623 A discloses a copper-based composite friction material containing modified sepiolite, as well as its preparation method and application. Natural sepiolite is subjected to high-temperature treatment in a vacuum sintering furnace to improve its thermal and structural stability through thermal decomposition, dehydration, and structural changes. However, when a vehicle brakes, the copper-containing friction material produces a large amount of copper dust as the friction material wears, resulting in heavy metal pollution. Currently, no method has been developed to synthesize friction materials with superior performance by organically modifying sepiolite to form a matrix with an organic material such as a resin.
[0011] Based on the above background, there is still a lack of a simple and efficient method for preparing dry organic modified clay and applying it to the reinforcing fiber material of friction materials. Summary of the Invention
[0012] To address these issues, the present invention proposes an oleophilic sepiolite, its preparation method, and its application. Using fibrous sepiolite as a representative clay, this method addresses the shortcomings of clay minerals, such as low surface organication, high modification costs, and poor modification results. This method combines traditional thermal activation treatment with dry ball milling, shortening the process and significantly improving production efficiency, offering significant practical guidance.
[0013] The present invention is achieved by the following technical solution: a method for preparing oleophilic sepiolite, comprising the following steps: (1) pre-mixing sepiolite and stearic acid and heating them to form a mixture of sepiolite and stearic acid, and removing adsorbed water in the sepiolite structure by thermal action; (2) The mixture of sepiolite and stearic acid is placed in a ball mill and ball mill beads are added. The ball mill is heated to ≥69.6°C to melt the stearic acid and further thermally activate the sepiolite. (3) After the preheated tank is taken out, γ-aminopropyltriethoxysilane, a clay surface modifier, is added, the mixture is fully mixed and ball milled, and after the ball milling is completed, the ball milling product is filtered to screen out the ball milling beads to obtain lipophilic sepiolite.
[0014] Furthermore, in step (1), the mass percentage of stearic acid in the mixture of stearic acid and sepiolite is 1-20 wt.%; the sepiolite and stearic acid are heated at a heating rate of 5°C / min, and the temperature is raised to 50-100°C for 10-60 minutes.
[0015] In step (2), the mass of the ball milling beads added is 4-6 times that of the mixture of sepiolite and stearic acid, and the ball milling jar is heated at a rate of 5°C / min to 100-150°C for 10-60 minutes.
[0016] In step (3), the γ-aminopropyltriethoxysilane accounts for 1-10 wt.% of the total mass of the mixture of sepiolite and stearic acid and the γ-aminopropyltriethoxysilane; the ball milling jar speed is 100-1000 r / min, and the ball milling is 10-60 min.
[0017] The present invention also provides oleophilic sepiolite obtained by the method.
[0018] The present invention also provides the use of the oleophilic sepiolite as a reinforcing fiber in a resin-based friction material.
[0019] The present invention also provides the use of the oleophilic sepiolite as a reinforcing fiber in a polyurethane-based material.
[0020] The present invention mixes γ-aminopropyltriethoxysilane into sepiolite as another clay surface modifier, which exerts a synergistic modification effect with melted stearic acid. The ball milling jar of a traditional planetary ball mill is heated to a temperature above the liquidus line of stearic acid (69.6°C), melting the stearic acid and further thermally activating the sepiolite. The modifier organically modifies the sepiolite, and after passing through a sieve made of wire mesh, the ball milling beads remain on the sieve, thereby achieving a filtering effect.
[0021] In the present invention, sepiolite and stearic acid are premixed in a beaker, with the mass percentage of stearic acid in the mixture of sepiolite and stearic acid being 1 to 20 wt.%. A mass percentage below 1 wt.% will not achieve a modification effect, and a mass percentage above 20 wt.% will exceed the amount required for surface coating and adsorption of the sepiolite. The sepiolite and stearic acid are preheated at a temperature of 50 to 100°C. Temperatures below 50°C fail to remove the adsorbed water in the sepiolite structure, and temperatures above 100°C cause the stearic acid to melt prematurely, affecting the removal of the adsorbed water. The preheating time for the sepiolite and stearic acid is 10 to 60 minutes. If the time is less than 10 minutes, the adsorbed water in the sepiolite structure is poorly removed, and if the time is greater than 60 minutes, the adsorbed water removal effect is also ineffective, resulting in energy waste and increased costs.
[0022] The ball mill is heated to a temperature of 100-150°C. Temperatures below 100°C prevent the stearic acid from melting, while temperatures above 150°C far exceed the melting point of stearic acid, resulting in wasted energy and increased costs. The ball mill should be heated for 10-60 minutes. If the heating time is less than 10 minutes, the stearic acid will not melt effectively, and if the heating time is above 60 minutes, the stearic acid will not melt effectively, resulting in wasted energy and increased costs.
[0023] The mass of the ball milling beads is 4-6 times that of the milling material. If the mass of the ball milling beads is less than 4 times that of the milling material, the efficiency of sepiolite particle crushing is very low. If the mass of the ball milling beads is more than 6 times that of the milling material, the self-wear between the grinding balls will be increased, which to some extent reduces the interaction between the balls and the material, and thus increases energy consumption. γ-Aminopropyltriethoxysilane accounts for 1-10 wt.% of the total mass of the sepiolite, stearic acid mixture and γ-aminopropyltriethoxysilane. A mass percentage below 1 wt.% will not have any modification effect, and a mass percentage above 10 wt.% will exceed the amount required for surface coating and adsorption of the sepiolite.
[0024] The ball milling speed should be between 100 and 1000 r / min. Speeds below 100 r / min will prevent the modifier from being fully and evenly dispersed on the sepiolite surface, while speeds above 1000 r / min will damage the sepiolite's fiber structure. The ball milling time in the milling jar should be between 10 and 60 minutes. If the time is below 10 minutes, the modification effect will be insignificant, while if it is above 60 minutes, the fiber structure of the sepiolite will be damaged.
[0025] After the preheating step, the present invention can melt stearic acid as a dilution aid for γ-aminopropyltriethoxysilane, thereby improving the dispersion of γ-aminopropyltriethoxysilane on the surface of sepiolite, and can also thermally activate the sepiolite to a certain extent, thereby increasing the molecular thermal motion speed, enhancing the molecular activity, and improving the surface coating and adsorption efficiency of the combined modifier.
[0026] Compared with the current wet modification process with its long process, high energy consumption, high protection requirements and high equipment demand, the dry modification process: no solvent needs to be added, thus avoiding environmental pollution and energy waste; the modifier can be fully adsorbed on the powder surface, thus improving its utilization rate; the process flow is shorter and the operation is simpler; the equipment for dry modification has lower production protection requirements and higher safety; the process time can be flexibly adjusted within a larger range to meet the needs of different products.
[0027] Ball milling modification can achieve the following effects: refine the sepiolite mineral particles and significantly increase the surface area of the material, which is conducive to more reactions between the material and other substances, thereby improving the performance of the material; directly improve the various properties of the sepiolite mineral material, which can increase the compressive strength of the sepiolite mineral material and enhance the wear resistance of the sepiolite mineral material; by placing the ball milling medium (such as steel balls) and the material into the ball mill, the mechanical action of the ball mill is used to subject the material to multiple forces such as grinding, impact and friction, thereby achieving its refinement and homogenization. This refinement and homogenization is not only reflected in the particle size, but also includes improvements in particle morphology and distribution.
[0028] In summary, the present invention combines traditional heat treatment and dry ball milling modification, leveraging the technical advantages of both methods. This significantly improves preparation efficiency while maintaining the superior performance of the material. The resulting modified clay material exhibits a significantly increased contact angle with water, exhibits a completely floating distribution in water, and can be deeply integrated with other organic carrier materials to form various clay composites. The raw materials used in the present invention are environmentally friendly, and the process is simple to operate, making it suitable for large-scale industrial production.
[0029] The reaction principle of the present invention: the melting point of stearic acid is 69.6°C. It exists in solid form at room temperature and is difficult to be fully and evenly coated on the surface of clay. However, in the present invention, the heating stage can provide a temperature of 100-150°C to melt the stearic acid and coat the surface of sepiolite. Stearic acid can be used as a diluent for γ-aminopropyltriethoxysilane. The two are mutually soluble and together realize the synergistic effect of the modifier, and its effect is better than the use of a single modifier. Ball milling uses multiple forces such as grinding, impact and friction to prepare products of target particle size through crushing and grinding and mixing. The first high-temperature action is to remove the adsorbed water of sepiolite; the second high-temperature action is to melt the stearic acid and cooperate with γ-aminopropyltriethoxysilane for organic modification. The heating operation at different temperatures in stages meets the actual production conditions and is applicable to generalization. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a process flow chart of the present invention; Figure 2 Middle: (a) is the distribution state of sepiolite ore in water; (b) is the distribution state of oleophilic sepiolite in water; Figure 3 Middle: (a), (b), (c) are SEM images of sepiolite ore; (d), (e), (f) are SEM images of oil-wet sepiolite; Figure 4 Middle: (a) is the ball milling crushing effect diagram of sepiolite ore; (b) is the ball milling crushing effect diagram of oleophilic sepiolite; Figure 5 Middle: (a) and (b) are micro-region composition analyses of sepiolite ore; (c) and (d) are micro-region composition analyses of oil-wet sepiolite; Figure 6 The results of contact angle tests are shown in the figure: (a) is sepiolite ore, (b) is oleophilic sepiolite; Figure 7 The XRD spectra of sepiolite ore and oleophilic sepiolite; Figure 8 The infrared spectra of original sample and oil-wet sepiolite; Figure 9 Contact angle test results; in the figure: (a) is sepiolite ore, (b) is stearic acid-modified sepiolite, (c) is stearic acid and γ-aminopropyltriethoxysilane combined modified oleophilic sepiolite, (d) is the contact angle between the combined modified oleophilic sepiolite and the oil phase; Figure 10 Figure 3: The morphology of the friction material and the dual disc before and after the test. (a) is the friction material before the test; (b) is the dual disc before the test; (c) is the friction material after the test; (d) is the dual disc after the test. Figure 11 This is a scanning electron microscope-energy spectrum diagram of the interface of sepiolite reinforced friction material; Figure 12 This is the SEM image of the sample after wear; Figure 13 Middle: (a) Effect of sepiolite modification on friction coefficient at different temperatures, (b) Effect of sepiolite modification on wear rate at different temperatures; Figure 14 Mechanical strength of sepiolite / polyurethane composites; Figure: (a) Effect of different modified sepiolite content on the uniaxial compressive strength of the composite; (b) Stress-strain curve of polyurethane material standard sample; (c) Stress-strain curve of composite materials at different modified sepiolite content; Figure 15 Middle: (a) is the SEM image of polyurethane material, (b) is the SEM image of sepiolite ore / polyurethane composite material, and (c) is the SEM image of modified sepiolite / polyurethane composite material. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0033] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0034] The experimental methods in the following examples, unless otherwise specified, are all conventional methods. The instruments and equipment used in the following examples, unless otherwise specified, are all conventional laboratory instruments and equipment; the experimental materials used in the following examples, unless otherwise specified, are all purchased from conventional biochemical reagent stores.
[0035] The high-grade sedimentary sepiolite powder used in the examples was provided by Xiangtan Sepiolite Technology Co., Ltd., China; stearic acid was purchased from Tianjin Damao Chemical Reagent Factory (CAS No. 57-11-4, analytical grade AR); 3-aminopropyltriethoxysilane was purchased from Guangdong Dongguan Kangjin New Materials Technology Co., Ltd. (CAS No. 919-30-2, purity ≥99.1%); the ball milling beads were zirconia balls provided by Changsha Miqi Instrument Equipment Co., Ltd., with specifications of 5 / 8 / 10 mm, and the matching 250 ml ball milling jar was used.
[0036] Example 1: A method for preparing oleophilic sepiolite, comprising the following steps: Step 1: pre-mixing sepiolite and stearic acid in a beaker and heating them in an oven at 60° C. for 30 minutes to form a mixture of sepiolite and stearic acid with a stearic acid mass fraction of 15 wt.%; Step 2: Place the mixture of sepiolite and stearic acid in a ball mill, heat the ball mill at 130°C for 30 minutes, and place ball mill beads with a mass five times that of the ball mill material; Step 3: After taking out the preheated tank, add γ-aminopropyltriethoxysilane and mix thoroughly. The γ-aminopropyltriethoxysilane accounts for 5wt.% of the total mass of the mixture of sepiolite and stearic acid and the γ-aminopropyltriethoxysilane. Step 4: The mixture of sepiolite and stearic acid, γ-aminopropyltriethoxysilane and ball milling beads are ball milled in a planetary ball mill at a speed of 600 r / min for 40 minutes. After the ball milling, the ball milling product is filtered to screen out the ball milling beads to obtain lipophilic sepiolite.
[0037] The oleophilic sepiolite prepared in the above steps was subjected to relevant tests, and the test results and analysis are as follows: The distribution of sepiolite ore and prepared oleophilic sepiolite in water is as follows Figure 2 As shown. Figure 2 It can be seen that the sepiolite ore is distributed in the aqueous phase system in a suspended liquid state, showing a hydrophilic state; the oleophilic sepiolite after surface organic modification is in a hydrophobic state and floats on the surface of the water.
[0038] The SEM images of sepiolite ore and prepared oil-wet sepiolite are shown in Figure 2. Figure 3 and Figure 4 As shown. Figure 3 It can be seen that the raw sepiolite is in the form of long fiber rods with a fiber length of about 0.2-2μm, a disordered surface, and a rich specific surface area. However, after high-temperature ball milling modification with stearic acid and γ-aminopropyltriethoxysilane, the mineral particle size at the 1μm scale is significantly reduced, showing the crushing effect of the ball milling operation; at the 200nm scale, it can be clearly seen that under the uniform coating of the modifier, the sepiolite fibers are aggregated and compacted, showing the reason why the sepiolite property changes from hydrophilic to lipophilic; at the 100nm scale, it can be further compared that the breakage of the sepiolite fibers is shortened, and the short fibers are bonded and aggregated. Figure 4 It can be seen that under the Inlens detector of the SEM, further comparison shows that the mechanical action of the ball mill causes the sepiolite to be subjected to multiple forces such as grinding, impact and friction, thereby achieving its refinement and homogenization. This refinement and homogenization is not only reflected in the particle size, but also includes the improvement of particle morphology and distribution.
[0039] The sepiolite ore and the prepared oleophilic sepiolite were observed and located by SEM, and the micro-area chemical composition analysis of the selected ore sample area was performed by EDS, such as Figure 5 As shown in the figure, the main elements before modification are silicon, oxygen and magnesium, and carbon is the background value of the SEM stage. After high-temperature ball milling, nitrogen appears and the content ratio of carbon and oxygen increases, which proves that the organic modifier (C 18 H 36 O2 and C9H 23 NO3Si) to effectively adhere and coat the surface of sepiolite.
[0040] The contact angle test results of sepiolite ore and prepared oleophilic sepiolite are as follows: Figure 6 As shown in the figure, by optimizing the modifier addition amount and preheating temperature, the contact angle of the material increased from the initial hydrophilic 30.66° to 87.14°, rendering the sepiolite powder surface hydrophobic. Furthermore, the contact angle of the lipophilic sepiolite with polyester polyol was also tested. However, due to the good liquid absorption of the lipophilic sepiolite, the droplets were quickly absorbed by the sample, fully demonstrating that the organic modification of the sepiolite was successful, rendering it lipophilic.
[0041] The XRD spectra of sepiolite ore and prepared oleophilic sepiolite are as follows: Figure 7 As shown by Figure 7 It can be seen that the weakening of the characteristic peak of sepiolite indicates the weakening of its crystal form, which is consistent with the SEM image results.
[0042] The infrared spectra of sepiolite ore and prepared oleophilic sepiolite are as follows Figure 8 As shown, the infrared spectrum adsorption bond results are shown in Table 1.
[0043] Table 1 Infrared spectrum adsorption bond analysis Example 2: The organically modified clay material was prepared according to the steps of Example 1, but the process-related parameters were adjusted. The sedimentation rate and contact angle of the prepared organically modified clay material were tested after being placed on the surface of pure water for 5 minutes. The process-related parameters and the sedimentation rate and contact angle test results are shown in Table 2.
[0044] Table 2: Comparison of process-related hydrophobic properties of samples 1 to 19 in Example 2 Depend on Figure 8 As shown in Table 2, at wave numbers greater than 3000 cm -1 The high-frequency region is mainly the stretching vibration region of the surface hydroxyl groups, adsorbed water and crystal water of sepiolite, 3564 cm -1 The absorption peak at 3564 cm is attributed to the stretching vibration of the crystal water (OH2) of sepiolite. -1The decrease of the absorption peak at 2919 cm-1 proves the effect of the preheating step in the modification operation. -1 The adsorption peak corresponds to the antisymmetric stretching vibration of -CH2-, appearing at 2852 cm -1 The adsorption peak is attributed to the symmetrical stretching vibration of -CH2- and appears at 1467 cm -1 The adsorption peaks correspond to -CH3 or -CH2- bending vibrations. Compared with the original sepiolite, the appearance and enhancement of the above new peaks indicate the success of the modification with stearic acid and γ-aminopropyltriethoxysilane. The modified agent molecules may be adsorbed on the surface of sepiolite or react with the hydroxyl groups and Lewis acid centers on the surface of sepiolite. -1 The low- and medium-frequency regions are mainly caused by the bending vibration of the crystal water inside the sepiolite and the stretching vibration of the Si-O bonds in different structures in the sepiolite, which appear at 1667 cm -1 The absorption peak of crystalline water is the bending vibration, which is close to 3564cm -1 The absorption peaks at 1210 cm and 1210 cm are similar, which together illustrate the necessity of the preheating step; -1 The subsequent absorption peaks all involve the crystal structure of sepiolite itself. The consistent decrease in their peak values shows that the introduced modification agent molecules are evenly and comprehensively coated on the surface of sepiolite, fully demonstrating the superiority of high-temperature ball milling technology for organically modified clay minerals.
[0045] As can be seen from the data in Table 2, an orthogonal test was performed on six process parameters, including the preheating temperature of the oven, the mass percentage of stearic acid in the mixture of sepiolite and stearic acid, the heating temperature of the ball mill, the total mass percentage of the mixture of sepiolite and stearic acid and γ-aminopropyltriethoxysilane, the rotation speed of ball milling, and the time of ball milling. After the hydrophobic performance test, the preheating temperature of the oven used in Example 1 was 60°C, the mass percentage of stearic acid in the mixture of sepiolite and stearic acid was 15wt.%, the heating temperature of the ball mill was 130°C, the total mass percentage of γ-aminopropyltriethoxysilane in the mixture of sepiolite and stearic acid and γ-aminopropyltriethoxysilane was 5wt.%, the rotation speed of ball milling was 600r / min, and the time of ball milling was 40 min. As the optimal process parameters, the sedimentation rate of the prepared oleophilic sepiolite material reached 0% and the contact angle reached 87.14°.
[0046] Example 3: The steps of Example 1 were followed, but the control variables were a single modifier (only 15 wt.% stearic acid) and a combined modifier (15 wt.% stearic acid and 5 wt.% γ-aminopropyltriethoxysilane), and the contact angle of the prepared organically modified clay material was tested. The contact angle test results are shown in FIG. Figure 9 shown.
[0047] like Figure 9 It can be seen that the contact angle of the material is changed from the initial hydrophilic 28.54° ( Figure 9 a) increased to 72.29° ( Figure 9 b); The contact angle was further increased to 91.43° by combining 15wt.% stearic acid and 5wt.% γ-aminopropyltriethoxysilane as organic surface modifiers ( Figure 9 c), making the surface of sepiolite powder hydrophobic, the contact angle of oil droplet on the modified sepiolite surface is 49.84° ( Figure 9 d) is in a lipophilic state.
[0048] Example 4: To compare and illustrate the effects of raw and modified sepiolite on the friction properties of resin-based materials, 13 wt.% raw and modified sepiolite were used as reinforcing fibers in a resin-based friction material. The remaining raw materials were as shown in Table 3, along with 9.0% phenolic resin and 3.0% nitrile rubber as binders; 15.0% steel fiber and 0.8% aramid fiber as auxiliary fibers; 8.0% tire powder and 4.0% coke powder as additives; 5.0% graphite as an anti-wear and anti-friction agent; 1.2% alumina to increase the friction coefficient and reduce the wear rate; and 39% barite as a filler. 2.0 kg of the raw materials were added to a mixer and mixed for 30 minutes at a speed of 800 rad / min. The mixed sample is then removed and 330g of the mixture is weighed and poured into the mold. The hot press is then operated to press the mixed sample at 20MPa and high temperature for 14 minutes, with a 7-minute hold period and 7-minute pressure and pressure reduction cycles. The pressed friction material is then removed. Finally, to further stabilize the brake pad material and enhance its heat resistance, the sample is placed in a heat treatment furnace at 190°C for 10 hours, resulting in a block of friction material.
[0049] Table 3: Friction material test formula / wt% The wear results of the prepared oleophilic sepiolite friction material were analyzed. The appearance of the friction material and its dual disc before and after the test is shown in the figure. Figure 10 As shown, Figure 10 a and 10b are before the test, Figure 10 c and 10d are after the test. The SEM-EDS results of the friction material before the test are as follows Figure 11 The SEM morphology of the friction specimen after wear is as follows: Figure 12 .Depend on Figure 10It can be seen that the dual discs remained basically unchanged after the test and were not damaged. The friction material did not show any cracking or peeling after the test, but there were obvious scratches on the surface after friction. The microscopic morphology, element distribution and content of the friction material surface need to be further analyzed and characterized using a scanning electron microscope combined with an energy spectrum analyzer. Figure 11 It can be seen that the components in the friction material are irregularly distributed. Figure 11 a It can be seen that the large black area is graphite lubricant, the light gray area is the iron fiber for reinforcement, and the dark gray area is a mixture of barite, sepiolite, alumina, binder and other fillers. The mixed area marked in the figure contains 29.18% C, which should be graphite lubricant, binder and other components; 3.51% Mg, 8.71% Si, which should belong to sepiolite fiber; 6.28% Fe, which should belong to iron reinforcement fiber; 9.18% Ba, 2.31% S, which should be filler barite; 1.67% Al, which should be alumina filler. It can be seen from the figure that it also contains a certain amount of Ca and other components, which should be carbonate impurities. In addition, from Figure 11 b It can be found that these fibers are well dispersed and mixed with other ingredients. Figure 12 It can be seen that the surface morphology of the friction material after friction is irregular, with various components distributed across the surface, and some components undergoing significant morphological changes. During the friction process, resin burns out and vaporizes, and fillers and various fibers fall off, forming pits. Finer non-metallic fillers, due to their poor conductivity, form white spots. Some areas of the worn surface are relatively smooth, primarily due to the organic components in the material. For example, the aramid fibers in the material partially decompose and carbonize at high temperatures, leading to adhesion and plastic deformation, forming a transfer film on the surface, making the worn surface smoother and improving the material's wear resistance. Because sepiolite fibers are very fine, they cannot be observed on the worn surface.
[0050] The mechanical properties and friction properties of the friction materials containing sepiolite ore and the prepared oleophilic sepiolite were tested respectively. The results are shown in Table 4, Table 5 and Figure 13 shown.
[0051] Table 4: Mechanical properties test results of friction materials Table 5: Friction performance analysis results of friction materials As can be seen from Table 4, the shear strength and compressive strain of the friction materials prepared before and after modification meet the requirements of national standards. As can be seen from Table 5, the increase in the wear rate of the friction material containing oleophilic sepiolite is significantly lower than that of the friction material containing unmodified sepiolite, which is sufficient to show that the modification creates a "bridging" effect between the inorganic sepiolite and the organic matter, connecting the two substances, thereby improving the bonding ability of the interface, which is manifested in a reduced wear rate in the friction material. Figure 13 a reveals the influence of modification on the friction coefficient of friction materials. As can be seen from the figure, with the increase of friction temperature, the friction coefficient of friction materials increases first and then decreases continuously. The friction coefficient of friction materials containing oleophilic sepiolite is slightly lower than that of unmodified sepiolite friction materials. Figure 13 As shown in Figure b, as the friction temperature increases, the material wear rate increases. The oleophilic sepiolite has a greater influence on the wear rate: at 100-250°C, the wear rate increases slowly with increasing temperature, and the modified and unmodified materials have little effect on the wear rate. However, when the temperature is above 250°C, the wear rate increases significantly, and the wear rate of the friction material containing unmodified sepiolite increases significantly. The wear rate of the friction material containing oleophilic sepiolite increases significantly less than that of the friction material containing unmodified sepiolite.
[0052] Example 5: In order to compare and illustrate the effects of sepiolite ore and oleophilic sepiolite on the mechanical properties of polyurethane-based materials, 0-10 wt.% sepiolite ore and oleophilic sepiolite were used as reinforcing fibers in polyurethane-based materials to prepare sepiolite / polyurethane composite materials, and their mechanical properties were tested. The test results are shown in Figure 5. Figure 14 shown.
[0053] Figure 14 a is the peak uniaxial compressive strength of the polyurethane composite material of sepiolite ore and oleophilic sepiolite at different dosages. The upper limit of the uniaxial compressive strength of the polyurethane material is about 8.21 MPa when no sepiolite is added. When the filler is sepiolite ore, the compressive strength of the composite material is greater than the compressive strength of the polyurethane (8.87 MPa) only when the dosage is 4 wt.%. This reflects that the hydrophilicity of the large number of Si-OH groups on the surface of sepiolite ore makes it very poorly compatible with the organic polymer polyurethane, resulting in a decrease in the strength of the composite material. When the filler is oleophilic sepiolite, the compressive strength of the composite material is higher than that of the polyurethane material, which fully demonstrates that the organic modifier optimizes the surface of sepiolite, enhances the interfacial bonding force between sepiolite and polyurethane, improves the compatibility between sepiolite and polyurethane, and optimizes the dispersion state and stability of sepiolite in the polyurethane system.
[0054] Figure 14Figures b and c show the stress-strain curves of the composites with different oleophilic sepiolite content. The uniaxial compression stress-strain images can be divided into four stages: linear elasticity, yielding, strain softening, and failure. In stage I, stress increases approximately linearly with increasing strain. The material deforms elastically, and failure does not occur. During this stage, the material deformation is very small. In stage II, as the axial strain accumulates, the stress changes slowly, and the deformation of the material transitions from elastic to plastic. During this stage, the internal cellular structure of the polyurethane begins to bend and deform. Because the polyurethane skin is stronger than the core, microcracks initially form within the material. As the strain continues to increase, the stress in the specimen slowly decreases, and the material exhibits strain softening. Therefore, stage III is the strain softening stage, during which the skin becomes more brittle, cracking occurs, and cracks develop throughout the material. This stage leads to stage IV, when the material fails. With increasing oleophilic sepiolite content, the peak strain of the composite decreases from 0.05 to 0.018. When the addition amount of oleophilic sepiolite is 0wt.% and 2wt.%, a double ductile-brittle transition appears in the stress-strain curve. With the increase of the oleophilic sepiolite content, this phenomenon gradually disappears, and the strain range of the plastic stage III experienced by the composite material gradually narrows.
[0055] Internal cross-sectional SEM images of polyurethane material, sepiolite ore / polyurethane composite material, and oleophilic sepiolite / polyurethane composite material are shown in Figure 2. Figure 15 As shown. Figure 15 It can be seen that the fracture surface of the polyurethane material is smooth and flat, with almost no wrinkles ( Figure 15 a); The fracture surface of the sepiolite ore / polyurethane composite material shows a large number of accumulated wrinkles ( Figure 15 b), which reflects the lack of good compatibility and interface bonding between the sepiolite ore and the polyurethane matrix, making it impossible for the sepiolite ore to be evenly dispersed in the polyurethane system; the fracture surface wrinkles of the oleophilic sepiolite / polyurethane composite material are more uniform and fine ( Figure 15 c), which shows that the organic modifier improves the dispersibility of sepiolite fibers in the polyurethane system, further proving that the oleophilic sepiolite and polyurethane have good compatibility and strong interfacial bonding, which is consistent with the compression test results.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing oleophilic sepiolite, characterized in that: The steps include: (1) premixing sepiolite and stearic acid and heating them to form a mixture of sepiolite and stearic acid, and removing adsorbed water in the structure of the sepiolite by thermal action; (2) The mixture of sepiolite and stearic acid is placed in a ball mill and ball mill beads are added, and the ball mill is heated to ≥69.6°C to melt the stearic acid and further thermally activate the sepiolite; (3) After the preheated tank is taken out, γ-aminopropyltriethoxysilane, a clay surface modifier, is added, the mixture is fully mixed and ball milled, and after the ball milling is completed, the ball milling product is filtered and the ball milling beads are screened out with a 100-mesh standard sieve to obtain oleophilic sepiolite.
2. The method according to claim 1, characterized in that: In step (1), the mass percentage of stearic acid in the mixture of stearic acid and sepiolite is 1-20wt.%; the heating rate of sepiolite and stearic acid is 5°C / min, and the temperature is raised to 50-100°C and heated for 10-60min.
3. The method according to claim 1, characterized in that: In step (2), the mass of ball milling beads added is 4-6 times the mass of the mixture of sepiolite and stearic acid, the ball milling jar is heated at a rate of 5°C / min, and the temperature is raised to 100-150°C for 10-60min.
4. The method according to claim 1, characterized in that: In step (3), the γ-aminopropyltriethoxysilane accounts for 1-10wt.% of the total mass of the mixture of sepiolite and stearic acid and the γ-aminopropyltriethoxysilane; the ball milling jar speed is 100-1000r / min, and the ball milling is 10-60min.
5. The method according to claim 1, characterized in that: In step (1), the mass percentage of stearic acid in the mixture of stearic acid and sepiolite is 15wt.%; the heating rate of sepiolite and stearic acid is 5°C / min, and the temperature is increased to 60°C; in step (2), the heating rate of the ball mill is 5°C / min, and the temperature is increased to 130°C; in step (3), γ-aminopropyltriethoxysilane accounts for 5wt.% of the total mass of the mixture of sepiolite and stearic acid and γ-aminopropyltriethoxysilane, the ball milling speed is 600r / min, and the ball milling time is 40min.
6. Oleophilic sepiolite obtained by the method described in any one of claims 1 to 5.
7. Use of the oleophilic sepiolite according to claim 6 as reinforcing fiber in resin-based friction materials.
8. Use of the oleophilic sepiolite according to claim 6 as reinforcing fiber in polyurethane-based materials.
Citation Information
Patent Citations
High-temperature and ball-milling modified SBA-15 molecular sieve material and preparation method thereof, propane dehydrogenation catalyst and preparation method and application thereof
CN112138705A
Attapulgite clay surface organic modification process
CN114950348A
Preparation method of ball-milled carbon nanotube modified aluminum-based composite material at high temperature
CN115780801A
Preparation method of mixed-dimension attapulgite clay-based lubricating oil antifriction additive
CN116253329A
Copper-based composite friction material containing modified sepiolite as well as preparation method and application of copper-based composite friction material
CN117448623A